Criminal Law Reform of The Existence of Article 378 of The Criminal Code in Land Cases : Case Study of Judgment No. 1154/Pid.B/2021/PN. JKT.SE - Fransiska Khatrine (CV. Publikasi Indonesia, 2024)
There is the criminalization of handling land disputes in Indonesia, such as in the case of Decision No. 1154/Pid.B/2021/PN. JKT.SE, namely Ir. Burhanuddin, who owns land with justifiable rights in the form of a Certificate of Ownership as a defendant and sentenced to imprisonment for 3 (three years), shows the need for criminal law reform against the existence of article 378 of the Criminal Code. With the normative juridical research method of the statutory approach, the author finds that the Criminal Act of Fraud 378 of the Criminal Code in the perspective of the Indonesian Criminal Law is connected with land regulations, explaining that Fraud, according to article 378 of the Criminal Code anyone who uses fraud or a series of lies to make someone give something, blame him, or cancel a debt but according to the legal principle lexes specialist systematic derogate lex generalis. While juridically, both the Civil Code and the Basic Agrarian Law do not specifically regulate if there is an error fraud in the sale and purchase of land rights, the sanction given by law is to cancel the sale and purchase deed with a claim for compensation because fraud in the deed of sale and purchase of land rights is not a criminal/criminal act that should be threatened with criminal sanctions but becomes Depenalization. The legal considerations in Decision No. 1154/Pid.B/2021/PN. JKT. SEL, reviewed in the renewal of the Indonesian Criminal Law, that the elements of fraud in the Criminal Code, namely objective and subjective elements of a person, can only be considered to have committed a criminal act of fraud as mentioned in Article 378 of the Criminal Code if all aspects are met. In this case, the perpetrator can only be sentenced according to his actions. Article 378 of the Criminal Code stipulates that someone who commits fraud must deceive the victim in a certain way, but in this case, the Civil Code and the Basic Agrarian Law does not explicitly regulate if there is an error.